1983
DOI: 10.1128/mcb.3.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock alters nuclear ribonucleoprotein assembly in Drosophila cells.

Abstract: Heterogeneous nuclear RNA is normally complexed with a specific set of proteins, forming ribonucleoprotein particles termed hnRNP. These particles are likely to be involved in mRNA processing. We have found that the structure of hnRNP is profoundly altered during the heat shock response in Drosophila cultured cells. Although hnRNA continues to be synthesized at a near-normal rate during heat shock, its assembly into hnRNP is incomplete, as evidenced by a greatly decreased protein content of the particles in Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…Protection of tri-snRNP levels in pretreated heat-shocked cells+ Cell extracts from wild-type (JN55) and mutant strains, as indicated above the lanes, were electrophoresed on nondenaturing polyacrylamide gels and transferred to nylon membranes+ The membranes were probed with a U6 specific DNA probe+ The positions of the U4/U6+U5 tri-snRNP, the U4/U6 and U6 snRNPs are indicated+ Lanes 1, 4, 7, 10: extracts from untreated cells (25 8C)+ Lanes 2, 5, 8, 11: extracts from cells pretreated at 37 8C for 45 min and subsequently heat shocked at 42 8C for 1 h (TT)+ Lanes 3, 6, 9, 12: extracts from cells heat shocked at 42 8C without a prior pretreatment at 37 8C+ B: Cell extracts from strain SL304A (HSP104 ) were electrophoresed for 7 h (see Materials and Methods) to illustrate the upward shift in the U4/U6+U5 and the U4/U6 snRNPs+ Lane 1: untreated cells (25 8C)+ Lane 2: cells treated at 37 8C for 45 min+ Lane 3: cells treated at 37 8C for 45 min and then heat shocked at 42 8C for 1 h+ Lane 4: cells heat shocked at 42 8C for 1 h+ in heat-shocked cells (Fig+ 2A, lane 3, see arrowheads)+ These species are also observed in untreated cells but in much lower amounts, which suggests that they are precursors of the U4/U6 and/or the tri-snRNP+ Thus, heat shock treatments may block the assembly of snRNPs or alternatively, may disassemble snRNPs into bona fide precursor species+ Pulse chase experiments will be required to differentiate between these two possibilities+ In general, the levels of snRNAs remain relatively constant following a heat shock: we observed no more than a twofold reduction in U4 and U6 snRNAs, whereas U5, U1, and U2 levels were less affected (data not shown)+ snRNPS do not appear to be the only RNPs affected by heat shock+ A number of studies have also reported alterations in hnRNP particles in heat-shocked cells (Mayrand & Pederson, 1983;Lutz et al+, 1988;Mähl et al+, 1989;de Graaf et al+, 1992;Buchenau et al+, 1997)+ Many of these alterations are associated with mRNA splicing inactivation (Gattoni et al+, 1996;Mahé et al+, 1997)+ Thus, the inactivation of mRNA splicing in heat-shocked cells appears to be multi-faceted, but specifically involves alterations in RNP complexes+…”
Section: Inactivation Of Mrna Splicing In Heat-shocked Cells Is Corrementioning
confidence: 84%
See 1 more Smart Citation
“…Protection of tri-snRNP levels in pretreated heat-shocked cells+ Cell extracts from wild-type (JN55) and mutant strains, as indicated above the lanes, were electrophoresed on nondenaturing polyacrylamide gels and transferred to nylon membranes+ The membranes were probed with a U6 specific DNA probe+ The positions of the U4/U6+U5 tri-snRNP, the U4/U6 and U6 snRNPs are indicated+ Lanes 1, 4, 7, 10: extracts from untreated cells (25 8C)+ Lanes 2, 5, 8, 11: extracts from cells pretreated at 37 8C for 45 min and subsequently heat shocked at 42 8C for 1 h (TT)+ Lanes 3, 6, 9, 12: extracts from cells heat shocked at 42 8C without a prior pretreatment at 37 8C+ B: Cell extracts from strain SL304A (HSP104 ) were electrophoresed for 7 h (see Materials and Methods) to illustrate the upward shift in the U4/U6+U5 and the U4/U6 snRNPs+ Lane 1: untreated cells (25 8C)+ Lane 2: cells treated at 37 8C for 45 min+ Lane 3: cells treated at 37 8C for 45 min and then heat shocked at 42 8C for 1 h+ Lane 4: cells heat shocked at 42 8C for 1 h+ in heat-shocked cells (Fig+ 2A, lane 3, see arrowheads)+ These species are also observed in untreated cells but in much lower amounts, which suggests that they are precursors of the U4/U6 and/or the tri-snRNP+ Thus, heat shock treatments may block the assembly of snRNPs or alternatively, may disassemble snRNPs into bona fide precursor species+ Pulse chase experiments will be required to differentiate between these two possibilities+ In general, the levels of snRNAs remain relatively constant following a heat shock: we observed no more than a twofold reduction in U4 and U6 snRNAs, whereas U5, U1, and U2 levels were less affected (data not shown)+ snRNPS do not appear to be the only RNPs affected by heat shock+ A number of studies have also reported alterations in hnRNP particles in heat-shocked cells (Mayrand & Pederson, 1983;Lutz et al+, 1988;Mähl et al+, 1989;de Graaf et al+, 1992;Buchenau et al+, 1997)+ Many of these alterations are associated with mRNA splicing inactivation (Gattoni et al+, 1996;Mahé et al+, 1997)+ Thus, the inactivation of mRNA splicing in heat-shocked cells appears to be multi-faceted, but specifically involves alterations in RNP complexes+…”
Section: Inactivation Of Mrna Splicing In Heat-shocked Cells Is Corrementioning
confidence: 84%
“…The process of mRNA splicing is extremely sensitive in vivo thermal inactivation in many different organisms (Bond & Schlesinger, 1986;Yost & Lindquist, 1986;Bond, 1988;Vogel et al+, 1995)+ Treatment of cells at sublethal heat shock temperatures for an hour or more results in a complete but reversible inactivation of mRNA splicing+ In heat-shocked HeLa cells, alterations in snRNPs have been correlated with the inactivation of mRNA splicing (Bond, 1988;Shukla et al+, 1990;Utans et al+, 1992)+ Alterations of hnRNP particles have also been observed in heat-shocked HeLa and Drosophila cells, suggesting that RNP particles, in general, are particularly sensitive to heat shock (Mayrand & Pederson, 1983;Gattoni et al+, 1996;Mahé et al+, 1997)+ Despite the numerous effects of heat on RNPs, studies have shown that in vitro splicing activity in extracts prepared from heat-shocked cells can be restored by the addition of a protein fraction consisting minimally of five proteins (Utans et al+, 1992)+ This fraction is capable of reassembling the U4/U6 and the U5 snRNPs into the U4/U6+U5 tri-snRNP, suggesting that the primary splicing defect in heat-shocked HeLa cells may be the lack of a functional tri-snRNP+…”
Section: Introductionmentioning
confidence: 99%
“…(Welch and Feramisco, 1984), and is consistent with cell fractionation and autoradiographic studies on Drosophila salivary gland and tissue-culture cells (Arrigo et al, 1980;Velazquez et al, 1980) and tomato cells (Neumann et al, 1984). Interestingly, at least one other heat shock protein (a mammalian hspl 1O) is found in nucleoli, both at normal and high temperatures (Subjeck et al, 1983 (Mayrand and Pederson, 1983) and have been reported to bind hsp70 (Kloetzel and Bautz, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, it has been established that this increased synthesis reflects enhanced transcription of heat shock genes (12,25,26,(28)(29)(30)(31). Transcriptional control is a general feature of the heat shock response in many organisms, and in addition, translational control has been described for Drosophila (20) and Xenopus oocytes (2).…”
mentioning
confidence: 99%